Productive Zakat as a Strategic Instrument for Achieving the Sustainable Development Goals - Alfin Maulana; Akhyar Siddiq; Auliya Ghazna Nizami (Journal of Economic, Management and Entrepreneurship, 2025)
Poverty and social inequality remain major challenges in achieving sustainable development, necessitating alternative instruments that promote inclusive economic empowerment. Productive zakat, as an innovative approach to zakat management, has strong potential to support the Sustainable Development Goals (SDGs). This study aims to analyze the role of productive zakat in supporting the achievement of the SDGs, particularly in poverty alleviation, economic growth, gender equality, and the reduction of social inequalities. This study employs a qualitative descriptive method through a literature review. Data were collected from national and international academic journal articles, zakat management regulations, and relevant publications of zakat institutions. The analysis focuses on examining the relationship between the implementation of productive zakat and SDG indicators. The findings indicate that productive zakat contributes substantially to increasing beneficiaries’ income and economic self-reliance through the provision of business capital, skills training, and continuous mentoring. In addition, productive zakat supports microenterprise development, job creation, enhanced women’s economic participation, and the reduction of social inequality at the community level. The implications of this study highlight the importance of strengthening governance, program integration, and impact-based evaluation to optimize productive zakat as a strategic instrument of Islamic economics in advancing the achievement of the SDGs and sustainable economic development.